Optimal control of stochastic systems in the case of continuous-discrete observation channels with memory; Automatic Control and Computer Sciences; Vol. 40, Iss. 6 - Demin N. S. Nikolas S. (2006, 2006)
A proof of the separation theorem in the problem of optimal control of stochastic systems over a set of realizations of processes with continuous and discrete time which possess memory of arbitrary multiplicity relative to the state vector of the system is presented. An informal example is considered.